Obesity and cognitive decline: role of inflammation and vascular changes - Nguyen, Jason C. D.; Killcross, A. Simon; Jenkins, Trisha A. (Frontiers in Neuroscience, 2014)
The incidence of obesity in middle age is increasing markedly, and in parallel the prevalence of metabolic disorders including cardiovascular disease and type II diabetes is also rising. Numerous studies have demonstrated that both obesity and metabolic disorders are associated with poorer cognitive performance, cognitive decline, and dementia. In this review we discuss the effects of obesity on cognitive performance, including both clinical and preclinical observations, and discuss some of the potential mechanisms involved, namely inflammation and vascular and metabolic alterations.